DAMPAK KEPEMIMPINAN PASRTISIPATIF DALAM PENGAMBILAN KEPUTUSAN MAJELIS GEREJA TORAJA, JEMAAT BATANGPALLI - Friska Paborong; Alfrida Lai’papa, Kalvianus Rembang Bua’, Melki Salinding, Nicodemus Minggu (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
The most common decision-making is done by a stakeholder or what is called a leader or head. There are quite a lot of inappropriate decisions from a leader because the model used is also inappropriate. The purpose of this study is to find out how the principle of participatory leadership in decision-making can be applied in various types of institutions or companies. The method used is a qualitative research method with a descriptive approach to describe the real conditions that actually occur in the middle of society. Data collection is done through literature studies, social analysis and interviews. The theories that are the author's references are theories about leadership, theories about the church and theories about participatory principles in an organization or institution. After conducting in-depth studies and research, the results obtained from this study are that the Toraja Church of the Batang Palli Congregation has succeeded in implementing the principle of participatory leadership in administrative management, so that it becomes an education for other institutions in bringing about organizational, institutional or company changes that are better